American Society of Clinical Oncology Clinical Practice Guideline Update on Chemotherapy for Stage IV Non–Small-Cell Lung Cancer - Azzoli, Christopher G. (American Society of Clinical Oncology, 2010)
ASCO published a guideline on use of chemotherapy in advanced stage non–small-cell lung cancer in 1997. The latest update covers treatment with chemotherapy and biologic agents and reviews literature from 2002 to 2009.